Oral Clinical Manifestations of Neurofibromatosis Type 1 in Children and Adolescents - Rossella Santoro; Claudia Santoro; Francesca Loffredo; Antonio Romano; Silverio Perrotta; Rosario Serpico; Dorina Lauritano; Alberta Lucchese (Applied Sciences, 2020)
Background: Neurofibromatosis 1 (NF1) is an autosomal dominant genetic disorder. The expression of NF1 is extremely variable considering the broad spectrum of mutations affecting the gene(s) responsible for the pathology. Aim: To investigate the prevalence of oral manifestations in a group of children affected by neurofibromatosis type 1. Design: 100 pediatric patients, with genetically confirmed NF1 were enrolled in this study and matched to a total of 100 healthy children. Clinical examination was used to investigate: dental caries, dental abnormalities, periodontal health, neurofibromas, malocclusions, and enamel defects. Results: Mann Whitney’s test concerning prevalence of dental caries resulted in a no significant difference between the two groups (p = 0.90); a significant difference was highlighted as regards the other kinds of manifestations as well: enamel defects (p = 0.01), neurofibromas (p = 0.0043) and poor oral hygiene (p = 0.0002) with a higher prevalence of these features in NF1 patients than healthy controls. Similar results come out, regarding dental abnormalities in which can observe a significant difference between shape anomalies (p < 0.001). Conclusion: According to data obtained from the present study, it can be stated that NF1-related oral manifestations can be detected during childhood and adolescence. In particular for neurofibromas, enamel defects, shape anomalies, and poor oral hygiene.